2005
DOI: 10.1017/s0012162205000484
|View full text |Cite
|
Sign up to set email alerts
|

A proposed classification for subtypes of arterial ischaemic stroke in children

Abstract: The aim of this study was to propose a classification system for childhood arterial ischaemic stroke (AIS). Subtypes from the Trial of Org 10172 in Acute Stroke Therapy (TOAST) classification, previously shown to be applicable to children, were retained in the proposed Paediatric Stroke Classification (PSC). Additional important paediatric AIS aetiologies were identified from a literature review. Preliminary validation was performed by three raters who categorized clinical vignettes from 135 patients (66 male;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 28 publications
(20 reference statements)
0
22
0
2
Order By: Relevance
“…13;14 Subsequent efforts toward childhood-specific nomenclature and classification in AIS have been proposed (The Pediatric Stroke Classification [PSC] and the Sebire Criteria), but no one system has been widely adopted. 15;16 …”
Section: Introductionmentioning
confidence: 99%
“…13;14 Subsequent efforts toward childhood-specific nomenclature and classification in AIS have been proposed (The Pediatric Stroke Classification [PSC] and the Sebire Criteria), but no one system has been widely adopted. 15;16 …”
Section: Introductionmentioning
confidence: 99%
“…Priority should be given to characterisation of the cerebral arterial circulation and to identification of potentially modifiable risk factors 3 11. In the present study, arteriopathies were identified in 10 of 29 patients (34.5%).…”
Section: Discussionmentioning
confidence: 57%
“…Patients were classified according to the previously proposed classification for subtypes of AIS in children11 and divided into two groups for analysis. Group I consisted of children with determined causes of AIS including arteriopathies and cardioembolism.…”
Section: Methodsmentioning
confidence: 99%
“…All patients with undetermined etiology had normal investigations including cerebrovascular imaging, echocardiogram, and prothrombotic studies [14,15]. …”
Section: Methodsmentioning
confidence: 99%